Proceedings of the 7th Scientific Conference on Information Technologies for Intelligent Decision Making Support (ITIDS 2019) 2019
DOI: 10.2991/itids-19.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

Computer Modelling of Organic and Inorganic Chemistry Processes

Abstract: This article describes the modelling software complexes are described that allow to determine such parameters of technological processes that can not be directly measured, but knowledge of which is necessary for conducting chemical processes in optimal modes for a given quality of the product. The imitation modelling software of the polymerization of vinyl chloride, which allows determining the molecular mass distribution of polymer molecules, describes a program for modelling the electrolyzer parameters in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In general, the results of the research showed that the level of air pollution with inorganic dust, carbon monoxide, nitrogen dioxide and hydrocarbons in the contract area does not exceed the MPC and the background indicators of the EA in 2017. It can be concluded that air does not experience an increased anthropogenic and techno genic load [16][17][18][19][20][21].…”
Section: Results Of Environmental Monitoring Of the State Of Atmospherementioning
confidence: 99%
“…In general, the results of the research showed that the level of air pollution with inorganic dust, carbon monoxide, nitrogen dioxide and hydrocarbons in the contract area does not exceed the MPC and the background indicators of the EA in 2017. It can be concluded that air does not experience an increased anthropogenic and techno genic load [16][17][18][19][20][21].…”
Section: Results Of Environmental Monitoring Of the State Of Atmospherementioning
confidence: 99%
“…Since it is an effective way to remotely control and monitor production processes using an automatic control system, this paper presents a method for controlling a reactor in a polyvinyl chloride production process using this system. It is desirable to transfer hot and cold water to the heat exchanger on the surface of the reactor using the recuperative heat exchange process to control the pressure and temperature when transferring substances to the reactor in series [11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the statement about the need to create a database for all available coals and the development of an algorithm for using this database to configure detectors can be considered fair. The next step in creating an artificial intelligence system to prevent spontaneous combustion of coal should be the organization of information exchange between producers, consumers, coal custodians and other interested enterprises [26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: System For the Prevention Of Spontaneous Combustion Of Coal ...mentioning
confidence: 99%